Diversity of reductive dechlorinating bacteria and archaea in herbicide/dioxin-contaminated soils from Bien Hoa airbase using metagenomic approach - Huy, Pham Quang; Kim Thoa, Nguyen; Thi Cam Ha, Dang (Vietnam Journal of Biotechnology, 2021)
Heavy herbicide/dioxin contamination of soil was derived a negative effect on the microbial biodiversity, soil quality, animal and human health in Central and South of Vietnam. This is the first time, the application metagenomic tools investigated soil microbial structural community of undetoxified (C - 21,605 ng TEQ/kg dry soil) and bioremediated (BHR - 13.2 ng TEQ/kg dry soil) which could not only help us to explore the potential risks associated with contaminated soils but also provide insights into possible soil bioremediation technology by stimulating indigenous microbes. Four methanogen genera, Methanosarcina (24 - 322 OTUs respectively C – BHR samples), Methanocella (13 - 63 OTUs), Methanosaeta (7 - 42 OTUs) and Methanococcus (6 - 69 OTUs) have been dominantly detected in both two metagenomes. Twenty genera of archaea belonging to the phylum Euryarchaeota were found. They could be clustered within 14 different families and nine archaeal genera including unclassified archaea (17 OTUs – C; 145 OTUs - BHR). In metagenome C and BHR, 12 genera of sulfate reducing bacteria (SRB) with different number (2 - 77; 61 - 904 OTUs) respectively were presented. Four SRB genera are dominated in C metagenome, it is linear also in BHR. The highest number is genus Desulfovibrio detected in both examined metagenomes. However, the relationship features of these bacterial groups need deeply investigation for understanding their role of reductive dechlorination, anaerobic degradation in herbicide/dioxin contaminated heavy soil and sediment. These results provide additional evidence to explain why heavy herbicide/dioxin contaminated soil was detoxified successfully at Bien Hoa airbase, Vietnam.